1977
DOI: 10.1677/joe.0.0720005
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vasopressin in the Mitotic Response of Rat Bone Marrow Cells to Haemorrhage

Abstract: Two days after a severe haemorrhage plasma calcium concentrations and bone marrow mitotic activity in rats were significantly increased and so remained for a further 5-6 days until the haematocrit had returned to normal. The first 48 h after bleeding were characterized by hypocalcaemia. During this phase two significant peaks in mitotic activity were observed at 4 and 18 h after haemorrhage. The mitotic surge 4 h after bleeding was still present in adrenalectomized and parathyroidectomized animals but in rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…It has been shown that VP stimulates mitogenesis in a number of systems, including mouse Swiss 3T3 cells (Rozengurt et al, 1979), rat bone marrow cells following hemorrhage (Hunt et al, 1977), rat liver cells (Russell & Bucher, 1983), mesangial cell (Ghosh et al, 2001), human osteoblastlike cells (Lagumdzija et al, 2004) and the murine corticotroph tumor cell line, AtT20 (van Wijk et al, 1995). VP has also been shown to increase the number of cells incorporating BrdU in primary cultures of rat anterior pituitary cells (McNicol et al, 1990).…”
Section: Alternative Actions Of Vp In the Pituitary On Mitogenesismentioning
confidence: 99%
“…It has been shown that VP stimulates mitogenesis in a number of systems, including mouse Swiss 3T3 cells (Rozengurt et al, 1979), rat bone marrow cells following hemorrhage (Hunt et al, 1977), rat liver cells (Russell & Bucher, 1983), mesangial cell (Ghosh et al, 2001), human osteoblastlike cells (Lagumdzija et al, 2004) and the murine corticotroph tumor cell line, AtT20 (van Wijk et al, 1995). VP has also been shown to increase the number of cells incorporating BrdU in primary cultures of rat anterior pituitary cells (McNicol et al, 1990).…”
Section: Alternative Actions Of Vp In the Pituitary On Mitogenesismentioning
confidence: 99%
“…The neurohormone vasopressin and the tetradecapeptide bombesin (1) are also potent mitogens. The former stimulates DNA synthesis in chondrocytes (26), bone marrow cells (18), and Swiss 3T3 mouse fibroblasts (34). The latter, which stimulates hormone secretion (37) and smooth muscle contraction and affects temperature control and behavior in mammals (14,38), shows potent mitogenic activity on Swiss 3T3 fibroblasts (35), in which high-affinity receptors for peptides of the bombesin family were recently demonstrated (45).…”
mentioning
confidence: 99%
“…Both vasopressin and oxytocin have replaced interleukin-2 (the T-cell growth factor) for y-interferon production by Lyt 2+ mouse lymphocytes (17). Although the neurohypophyseal peptides are not directly mitogenic for peripheral lymphocytes [(17) and personal observationsl, vasopressin stimulates DNA synthesis in bone marrow cells (18). Recently the role of several neuropeptides in the control of cell proliferation has been suggested (19).…”
mentioning
confidence: 99%